Bryophytes of the Santa Elena Peninsula and Islas Murciélago, Guanacaste, Costa Rica, with special attention to neotropical dry forest habitats - Dauphin, Gregorio; Grayum, Michael (Lankesteriana: International Journal on Orchidology, 2015)
Fifty-five bryophyte species (21 hepatics, 34 mosses) are reported from the dry lowland forests and moist montane forests of the Santa Elena Peninsula and Islas Murciélago, Guanacaste Province, Costa Rica. Over 50% of the collected species are neotropical, 16% have a pantropical distribution and 12% are amphiatlantic (America-Africa). Nine percent of the species are of limited distribution in potentially dry forest areas of Mexico, Cuba and Costa Rica. Brachymenium spirifolium, Fissidens juruensis var. juruensis, F. radicans, F. yucatanensis, Gymnostomiella vernicosa and Rhodobryum grandifolium are reported as new to Costa Rica. Uleobryum peruvianum and Cephaloziella subtilis are new to Central America. By far the most diverse bryophyte vegetation type in the study area is found above 500 m, in the moist montane forest of the Cerros Santa Elena. These moist forests support many corticolous bryophytes; however, soil, logs and rocks are the most important bryophyte habitats in the dry forests.